Resilient modulus of Malaysian base and subbase pavement materials - Ahmad Kamil, Arshad; Mohd. Yusof, Abd. Rahman, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/